Experimental Thermal Assessment of a Trombe Wall Under a Semi-Arid Mediterranean Climate of Mexico - Iván Hernández-Pérez; Álan Rodriguez-Ake; Daniel Sauceda-Carvajal; Irving Hernández-López; Balaji Kumar; Ivett Zavala-Guillén (Energies)
The conventional Trombe wall (TW) with concrete construction has been shown to enhance the indoor environment of buildings in cold and Mediterranean climates. Thus, a TW is an option for reducing energy consumption related to thermal comfort for buildings in the northwestern region of Mexico, characterized by arid and semi-arid conditions with low winter temperatures. The thermal behavior of the TW and a conventional facade (CF) of concrete were compared when installed in the southern wall of reduced-scale test boxes in Ensenada, B.C. Unlike other research works available in the literature, which typically monitored a data point measure of the wall and room temperatures, the present study measured the temperature of key components: the absorber wall, the air at the bottom and top vents, the glass cover, and the air at the cross-section plane of the TW test box. The results showed that the TW increases the air temperature through its channel up to <semantics>14 ∘</semantics>C and yields a maximum thermal efficiency of 84% during a sunny winter week. Further, the indoor air temperature at the midpoint of the TW test module is up to <semantics>6 ∘</semantics>C greater than the obtained on the CF-test module; therefore, the TW improved the thermal comfort conditions during winter.